A facile biosynthesis of copper nanoparticles: A micro-structural and antibacterial activity investigation - Y.T. Prabhu; K. Venkateswara Rao; V. Sesha Sai; Tambur Pavani (Journal of Saudi Chemical Society)
Nanostructured copper particles are synthesized by Garcinia mangostana leaf extract as reducing agent with copper nitrate. X-ray diffraction study confirms the formation of nanocrystalline cubic phase of copper nanoparticles. The micro-structural properties such as grain size, strain, dislocation density and particle size are examined. The lattice constant is calculated using Nelson–Riley function. Physical parameters like lattice constants, stress, strain, dislocation density and size are calculated. Differential thermal analysis (DTA) and thermo gravimetric (TGA) have confirmed that nanoparticles have phase purity and weight loss percentage is 3.328%. The particle size calculated from XRD is 26.51 nm which is in good agreement with the results of W–H plot, SSP methods and particle analyser. The morphology of prepared copper nanoparticles is characterized by scanning electron microscope (SEM) and TEM. These biologically synthesized nanoparticles are highly antibacterial against Escherichia coli and Staphylococcus aureus.